2019
DOI: 10.3390/ijms20225752
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Antibody Discovery Using Human Pluripotent Stem Cells: Conservation of Oncofetal Targets

Abstract: Pluripotent stem cells (PSCs) comprise both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). The application of pluripotent stem cells is divided into four main areas, namely: (i) regenerative therapy, (ii) the study and understanding of developmental biology, (iii) drug screening and toxicology and (iv) disease modeling. In this review, we describe a new opportunity for PSCs, the discovery of new biomarkers and generating antibodies against these biomarkers. PSCs are good sources of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Tumor cells hijack developmental signaling to gain lineage plas ticity and evolve toward drugrefractory identities. Oncofetal proteins, which are encoded by highly expressed genes during em bryonic development that are silenced in terminally differentiated cells, provide ideal targets for immunebased drug development, because these proteins are not present in normal healthy adult tis sue, reemerge in tumor cells, and tend to be immunogenic (20). Previously, we showed that human embryonic stem cells (hESCs) differentiated into mature hepatocytes along hepatic lineages using transcriptomic RNA sequencing (RNAseq) to profile the genes actively expressed during liver development but silenced in the mature hepatocytes (21).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells hijack developmental signaling to gain lineage plas ticity and evolve toward drugrefractory identities. Oncofetal proteins, which are encoded by highly expressed genes during em bryonic development that are silenced in terminally differentiated cells, provide ideal targets for immunebased drug development, because these proteins are not present in normal healthy adult tis sue, reemerge in tumor cells, and tend to be immunogenic (20). Previously, we showed that human embryonic stem cells (hESCs) differentiated into mature hepatocytes along hepatic lineages using transcriptomic RNA sequencing (RNAseq) to profile the genes actively expressed during liver development but silenced in the mature hepatocytes (21).…”
Section: Introductionmentioning
confidence: 99%
“…The review by Tan and Choo explores the application of pluripotent stem cells (PSCs) for the discovery of new biomarkers and generating antibodies against those biomarkers. The monoclonal antibodies generated against PSCs might have applications in cancer-targeted therapy to kill cancer cells, and conversely, monoclonal antibodies already in use in cancer might be repurposed for regenerative medicine, making it safer [11]. Grywalska et al review the use of currently available immune checkpoint inhibitors in cervical, endometrial, and ovarian cancers.…”
mentioning
confidence: 99%